The Effect of Using Storytelling On Student’ Speaking Skill at the Eight Grades of SMPN 28 Muaro Jambi - Marwiyah Marwiyah (Cahaya Ilmu Cendekia Publisher, 2021)
Purpose of the study: Storytelling can help the learners becomes more confident to express their ideas spontaneously and creatively. So, the researcher thought that may be this technique could help the researcher to solve the students’ speaking problems. The researcher gave a story and asked the students to retell the story with their own expression and language. Methodology: This research used quantitative design. This research was to find out the effect of using storytelling on students’ speaking skill. It was experimental research. The best type of testing hypotheses about cause effect is experimental research. It used quasi experimental design with were chosen two classes as two groups. Main Findings: Storytelling have positive effect toward students’ speaking ability. The result of the data analysis indicated that the students’ speaking skill in terms of pronunciation, grammar, fluency, and vocabulary have increased from the pretest to posttest. The result of posttest in experimental class is higher than in control class. Novelty/Originality of this study: The result of this research was expected to provide some significance and contributions in teaching and learning speaking English that had useful information. For students, storytelling could get input to develop students’ ability in speaking. Students also learned how to speak English well by storytelling.